Influence of Social Media Marketing Efforts on Brand Equity and Consumer Response to Branded Shoes in India - Menon, P. Balakrishnan (Indian Journal of Marketing, 2021)
The purpose of the study was to provide a framework that depicted how social media marketing activities influenced brand equity and consumer preference and response towards branded shoes in India. The study’s primary aim was to examine the influence of social media marketing activities on consumers’ responses through brand equity creation. The theoretical framework conceived for the study was tested using primary data collected from consumers who were using branded luxury shoes aged between 18 – 50 years in the state of Kerala. Partial least squares method and structural equation modeling were employed to analyze the data. The results validated that entertainment, trendiness, word-of-mouth, and interaction significantly impacted social media marketing efforts. Brand awareness, brand image, perceived quality, and brand association also significantly contributed to brand equity. The willingness to pay a premium price, brand preferences, and brand loyalty positively impacted consumer response behaviour. The derived model elaborately substantiated that the social media efforts influenced brand equity, which mediated preferential customer response, brand choice, and brand loyalty.